Ex vivo hemostatic and immuno‐inflammatory profiles of freeze‐dried plasma. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Peng, Henry T.; Rhind, Shawn G.; Devine, Dana; Jenkins, Craig; Beckett, Andrew
Abstract: Background: Hemorrhage is a leading cause of preventable death in civilian and military trauma. Freeze‐dried plasma is promising for hemostatic resuscitation in remote prehospital settings, given its potential benefits in reducing blood loss and mortality, long storage at ambient temperatures, high portability, and rapid reconstitution for transfusion in austere environments. Here we assess the ex vivo characteristics of a novel Terumo's freeze‐dried plasma product (TFDP). Study design and methods: Rotational thromboelastometry (ROTEM) tests (INTEM, EXTEM, and FIBTEM) were conducted on plasma samples at 37°C with a ROTEM delta‐machine using standard reagents and procedures. The following samples were analyzed: pooled plasma to produce TFDP, TFDP reconstituted, and stored immediately at −80°C, reconstituted TFDP stored at 4°C for 24 h and room temperature (RT) for 4 h before freezing at −80°C. Analysis of plasma concentrations of selected cytokines, chemokines, and vascular molecules was performed using a multiplex immunoassay system. One‐way ANOVA with post hoc tests assessed differences in hemostatic and inflammatory properties. Results: No significant differences in ROTEM variables (coagulation time [CT], clot formation time, α‐angle, maximum clot firmness, and lysis index 30) between the TFDP‐producing plasma and reconstituted TFDP samples were observed. Compared to control plasma, reconstituted TFDP stored at 4°C for 24 h or RT for 4 h showed a longer INTEM CT. Levels of immuno‐inflammatory mediators were similar between frozen plasma and TFDP. Conclusions: TFDP is equivalent to frozen plasma with respect to global hemostatic and immuno‐inflammatory mediator profiles. Further investigations of TFDP in trauma‐induced coagulopathy models and bleeding patients are warranted.